1893 Okla. Terr. Stat. 503, ch. 25, art. 45 § 2 - (:unkn) unknown (General Publisher, 1893)
Prohibited the carry of any pistol, revolver, Bowie knife, dirk knife, loaded cane, billy, metal knuckles, or any other offensive or defensive weapon.
--
Keywords: CARRY